2018
DOI: 10.1128/iai.00812-17
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune-Disease-Prone NOD Mice Help To Reveal a New Genetic Locus for Reducing Pulmonary Disease Caused by Mycoplasma pulmonis

Abstract: Mycoplasmas are bacterial pathogens of a range of animals, including humans, and are a common cause of respiratory disease. However, the host genetic factors that affect resistance to infection or regulate the resulting pulmonary inflammation are not well defined. We and others have previously demonstrated that nonobese diabetic (NOD) mice can be used to investigate disease loci that affect bacterial infection and autoimmune diabetes. Here we show that NOD mice are more susceptible than C57BL/6 (B6) mice to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Phenotypic variations of host response to M. pulmonis infection have been demonstrated in several inbred mouse strains(4,5,46) and autoimmune disease mouse(54). In Chapter 1, it was shown that classical inbred strains of mice manifested an extreme response, highly resistant or highly susceptible to M. pulmonis infection.…”
mentioning
confidence: 99%
“…Phenotypic variations of host response to M. pulmonis infection have been demonstrated in several inbred mouse strains(4,5,46) and autoimmune disease mouse(54). In Chapter 1, it was shown that classical inbred strains of mice manifested an extreme response, highly resistant or highly susceptible to M. pulmonis infection.…”
mentioning
confidence: 99%
“…Entire lung sections stained with H&E were automatically digitized and analyzed using the TissueFAXS200 tissue slide analysis system (TissueGnostics, Austria). These images were further evaluated based on a histopathologic inflammatory scoring system as described previously, 27 which has been widely employed to analyze many mouse models of respiratory infections 28,29 …”
Section: Methodsmentioning
confidence: 99%
“…These images were further evaluated based on a histopathologic inflammatory scoring system as described previously, 27 which has been widely employed to analyze many mouse models of respiratory infections. 28 , 29 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation